PENERAPAN METODE DMAIC DALAM MENINGKATKAN EFEKTIVITAS SISTEM ERP UNTUK PENGELOLAAN RAW MATERIAL PADA PROSES PRODUKSI DI PERUSAHAAN MANUFAKTUR - Vikaliana, Resista; Putri, Claudia Artika (Prodi Teknik Industri, Fakultas Teknik, 2025)
The implementation of the Enterprise Resource Planning (ERP) system has become an important solution in raw material management in manufacturing companies, including PT IMR Arc Steel. This study aims to analyze the effectiveness of ERP systems using the DMAIC (Define, Measure, Analyze, Improve, Control) method in improving the efficiency of raw material management in the production process. This method helps identify key issues, such as raw material quality mismatches and errors in stock recording, which impact the smooth production process. Through the implementation of the DMAIC stage, it was found that the ERP system is able to provide significant improvements in terms of coordination between departments, improve the quality of raw material management, and reduce errors in production. The improvement steps implemented in the improvement stage, such as improving quality checks and optimizing communication, have succeeded in improving the company's performance. Nevertheless, some challenges such as machine maintenance and storage capacity still require further attention. This study concludes that the implementation of the ERP system with the DMAIC method has been effective in increasing the efficiency of the production process at PT IMR Arc Steel, although continuous evaluation and improvement are needed for more optimal results.